High density polyethylene matrix composite as reinforcing agent in medium density fiberboards - Ritter de Souza Barnasky R.* (2020)
© The Author(s) 2020.This work provides a study about the incorporation of a high density polyethylene (HDPE) matrix composite in medium density fiberboards (MDF). A composite was processed in a single screw extruder with 5% of Pinus spp fibers in a HDPE matrix and applied as reinforcing agent in MDFs, as well as pure HDPE, in 11 different variations, using 12% of urea-formaldehyde resin and nominal density of 750 kg.m−3. The composite and the pure HDPE were analyzed by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The DSC results showed that both polymeric matrix and composite presented the same melting temperature but the composite had a reduced melting enthalpy and crystallinity due to thermal history. SEM analysis showed a well distribution of fibers on the composite. The results of technological properties of MDFs were compared to commercial MDF standards. The MDF reinforced with 40% of polymeric composite reached all minimum standard requirements, being the most recommended to be used as an alternative to conventional MDF, in terms of physical and mechanical performance.